The Effect of Mudharabah and Musyarakah Financing on Profitability of Islamic Banks in Indonesia - El, Iqbal Maulana; Masyhuri, Masyhuri; Yuliana, Indah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The study aims to determine the effect of Mudharabah and Musyarakah financing on profitability of Islamic banks in Indonesia. Profitability is measured by using ROA. The population used in this study is Islamic banks registered in Bank Indonesia from 2016 to 2020, and by using purposive sampling technique. The researchers obtained 8 Islamic banks that meet the criteria. The study uses MRA (Multivariate Regression Analysis) with the following results: the Mudharabah variable has a tcount = 5.812 and a ttable = 2.026 (tcount > ttable) with a significance level of 0.000001 < 0.05. Thus, H1 is accepted, Mudharabah has a significant positive effect on profitability of Islamic bank. The Musyarakah variable has a tcount = -3.120 and a ttable = 2.026 (tcount > ttable) with a significance level of 0.003498 < 0.05. Therefore, H2 is accepted, Musyarakah has a significant negative effect on profitability of Islamic banks.